Relationship Between Growth Differentiation Factor-15 Levels and Micro-Atrial Fibrillation - Orta, Hüseyin; Aydın, Cihan; Demirkıran, Aykut; Aykaç, Hüseyin; Yılmaz, Ahsen (The European Research Journal, 2026)
Objectives: Micro-atrial fibrillation (micro-AF) represents short, irregular supraventricular tachyarrhythmia episodes that may precede clinical atrial fibrillation (AF). Identifying biomarkers associated with micro-AF could improve early detection and risk stratification. Growth Differentiation Factor-15 (GDF-15), a stress-responsive cytokine related to inflammation and myocardial injury, has been associated with AF, but its relationship with micro-AF remains unclear. Methods: Ninety patients who underwent 24-hour Holter monitoring due to palpitations were enrolled. Forty-five patients with micro-AF and 45 controls without supraventricular tachyarrhythmia were compared. Serum GDF-15 levels and clinical characteristics were analyzed using standard statistical methods, including logistic regression analysis and Receiver Operating Characteristic (ROC) curve analyses. Results: The groups were similar in age, sex, and comorbidities. Prior stroke was significantly more frequent in the micro-AF group (28.8% vs. 6.7%, P<0.001). Mean serum GDF-15 levels were significantly higher in patients with micro-AF than in controls (544.2±322.5 vs. 344±138.8 pg/mL, P<0.001). Logistic regression revealed that GDF-15 was associated with stroke risk in univariate analysis but not independently in multivariate analysis. Conclusions: Elevated GDF-15 levels in individuals with micro-AF suggest an underlying inflammatory or structural atrial substrate, supporting its potential role as a biomarker for early arrhythmia detection and assessment of thromboembolic risk. Larger, prospective studies are warranted to clarify the prognostic significance of GDF-15 in micro-AF.